Studi literatur membandingkan pengaruh model pembelajaran terhadap pembentukan karakter siswa - Ma'la, Amril (Maliki Interdisciplinary Journal, 2023)
Character formation is a process of cultivation of high values and akhlakul karimah to students both by parents and teachers in school. In the world of school character formation can be done in learning activities using the model of learning taught. Learning model is the approach used in the learning activities in the classroom by the teacher to the student using media that supports learning activities. There are many types of learning models, such as Problem-Based Learning (PBL), Cooperative Learning, Project Based Learning, Contextual Teaching and Learning, Inkuiri Learning, and Concept Learning. The method in the preparation of this article is the study of literature, meaning the process of researching, selecting and thoroughly studying literature relevant to a particular research topic or question. Results of literary studies have shown that learning models that have an influence on student character formation are all student-focused learning models.